Failure process and support method of roadways excavated in inclined rockmass strata - Gao, Jinhai (Horizon Research Publishing, 2014)
A three-dimensional geomechanical physical model is first constructed according to the similar simulation theory for a roadway excavated in inclined rock mass strata. The similar simulation model is then loaded in the laboratory using a self-designed YDM-E physical model testing device to observe the stress distribution and associated failure process of the roadway. For the roadway excavated in the rockmass strata with an inclined angle of 25°, it is found that cracks are initiated firstly in the rockmass located in the right-upper corner of the roadway and then propagate and coalesce resulting in that the rock located in the right-upper corner of the roadway detaches from the roof and falls into the roadway causing the collapse of the roadway. An unsymmetrical supporting scheme is then proposed to use cablebolts to supplement the regular support system of shotcrete lining and rockbolts for the roadway excavated in the inclined rock mass strata, which ensures the stability of the roadway while saving the supporting costs. In the proposed unsymmetrical supporting scheme, additional cablebolts are installed in the direction where the failures and rock falls easily occur during the tunnelling of the roadway in the inclined rockmass strata. The proposed unsymmetrical supporting scheme is finally tested in a roadway excavated in the inclined rockmass strata of a coal mine. According to the continuous monitoring results in three months, it is found that the convergence between the roof and the floor of the roadway and that between the lateral walls become stable in about two months after the tunnelling of the roadway, and the separation of rock mass strata in both the rockbolt-reinforced zone and the cablebolt-reinforced zone is small, which indicates that the proposed unsymmetrical support scheme can ensure the stability of the roadway excavated in the inclined rockmass strata while keeping the supporting costs economical.